1999
DOI: 10.1007/s004030050408
|View full text |Cite
|
Sign up to set email alerts
|

FK506 and cyclosporin A inhibit stem cell factor-dependent cell proliferation/survival, while inducing upregulation of c-kit expression in cells of the mast cell line MC/9

Abstract: Murine mast cell proliferation and maturation are regulated by two distinct cytokines, interleukin-3 (IL-3) and the c-kit ligand, stem cell factor (SCF). In this study using cells of the mouse mast cell line, MC/9, the effects of two immunosuppressants, FK506 and cyclosporin A (CsA), were investigated. Withdrawal of IL-3 from the culture medium resulted in loss of viability of MC/9 cells. The addition of SCF in the absence of IL-3 maintained MC/9 cell survival but no cell proliferation was detected. The combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…FK506 also has suppressive effects on the proliferation of mast cells through the c-kit-MAP kinase pathway. 19 These observations suggest that corticosteroids and FK506 may have a direct effect on mast cells in human conjunctival tissue. In this study, in comparison with mast cell density in the 16W-group, mast cell density in the Dx group was decreased, but in the FK506 group, there was no significant change.…”
Section: Discussionmentioning
confidence: 96%
“…FK506 also has suppressive effects on the proliferation of mast cells through the c-kit-MAP kinase pathway. 19 These observations suggest that corticosteroids and FK506 may have a direct effect on mast cells in human conjunctival tissue. In this study, in comparison with mast cell density in the 16W-group, mast cell density in the Dx group was decreased, but in the FK506 group, there was no significant change.…”
Section: Discussionmentioning
confidence: 96%
“…Tacrolimus and CsA were found to inhibit the SCF dependent, but not the IL-3 dependent stimulatory effects on MC/9 cell proliferation/survival through inducing apoptosis directly. However, SCFmediated signal transduction in MC/9 cells, including c-Kit tyrosine phosphorylation and MAP kinase nuclear translocation, were not affected by tacrolimus or CsA treatment [30]. Concluded, calcineurin inhibitors can selectively inhibit SCF-dependent mast cell proliferation/survival and induce mast cell apoptosis, but only some of the SCF-mediated signaling pathways were affected by these drugs.…”
Section: Pimecrolimus Causes Mast Cells Depletion By Induction Of Apomentioning
confidence: 91%
“…the numbers of mast cells in the above mentioned diseases or disease models, which is in discordance with their effects in mastocytosis. We propose the hypothesis that the observed effects may be explained by differential effects of calcineurin inhibitors hyperproliferative mast cells induced by SCF [30] but not act on the hyperactive mast cells induced by the allergens. Future scaled-up clinical studies should verify, whether the above hypothesis is correct or not.…”
Section: Application Of Pimecrolimus and Other Topical Calcineurin Inmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to being a T-cell immunosuppressive agent, cyclosporine has also been shown to block mast cell proliferation and inhibit histamine release from mast cells. 12,13 Confino and Brown 8 in 1987 reported that 6 of 8 patients with SLK showed marked improvement or complete resolution with topical cromolyn sodium 4% therapy. In 1995, Grutzmacher et al 9 reported 3 cases with typical SLK presentation.…”
mentioning
confidence: 97%